Recourse versus non-recourse mortgage debt and costly state verification - Peter Mihaylovski (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2025)
This paper explores how policies that allow lenders to pursue borrowers for remaining debt after mortgage foreclosure (mortgage recourse) influence key aspects of the housing market and the broader macroeconomy. To this end, I develop a dynamic stochastic general equilibrium (DSGE) model featuring savers and borrowers, strategic default behavior on housing debt, and an endogenous loan-to-value (LTV) ratio. The analysis indicates that real house prices, LTV ratios, and mortgage debt levels increase with greater recourse tightness, while mortgage spreads decline. Default rates also increase with stricter recourse, despite more severe penalties targeting borrowers' assets beyond their housing collateral. In addition, mortgage recourse amplifies the volatility of key financial variables - such as LTV ratios, default rates, and mortgage spreads - intensifying financial cycles. Finally, mortgage recourse appears to be welfare-enhancing only for savers, as it provides an insurance-like mechanism in the event of borrower default. These findings underscore the complex tradeoffs involved in mortgage recourse policies, offering important insights into their role in shaping housing markets and, more broadly, economic stability.
Keywords: E32; E44; G01; R31; 330; DSGE; housing; recourse